Dinamika Kebebasan Berekspresi dan Ketertiban Umum: Studi Kasus Vandalisme di Daerah Istimewa Yogyakarta (DIY) dalam Perspektif Hukum - Dyah Retna Prabaningrum; A. Fahru Rozi (LPPM Universitas Ekasakti, 2026)
This study aims to assess the effectiveness of law enforcement related to vandalism in DIY and formulate a stronger regulatory model. Reports of vandalism are still rampant in DIY, but data from the DIY Regional Police regarding vandalism occurring in the working areas of the police stations under its jurisdiction are not directly proportional. From this, the effectiveness of law enforcement related to vandalism in DIY was tested using Lawrence Friedman's theory and Gustav Radbruch's theory. This study was conducted using empirical legal research methods. The results of the study found that existing regulations in DIY are not yet effective in overcoming vandalism. Law enforcement remains weak due to a legal structure and culture that is not yet strong. In fact, in substance, the regulations are clear and provide legal certainty. However, because their implementation is not yet optimal, the community has not felt the justice and benefits of these regulations. A possible solution is to create a special regional regulation on vandalism. This regional regulation can emulate Singapore's Vandalism Act with local adjustments. The regulation must provide a clear definition of vandalism and its enforcement can involve the Public Order Agency (Satpol PP), supported by the police for serious cases. Penalties can include fines, community service, or minor criminal offenses that still have a deterrent effect. The role of social services is also important, especially in guiding youth gangs and street children. The government also needs to provide spaces for expression, such as art studios or street art zones.